2016
DOI: 10.18632/oncotarget.9741
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA GAPLINC promotes invasion in colorectal cancer by targeting SNAI2 through binding with PSF and NONO

Abstract: This study aimed to investigate the role of long noncoding RNAs (lncRNAs) in the metastasis of colorectal cancer (CRC). Metastasis is an important prognostic factor of CRC, and lncRNAs have been implicated in tumor proliferation and metastasis. The human CRC cell lines HCT116, HT29, SW480, DLD-1, and SW620 were used in the study. Genome-wide lncRNA expression patterns in metastatic lymph nodes compared with paired normal lymph nodes of CRC were assessed by microarray analysis. Gastric adenocarcinoma predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 33 publications
4
50
0
2
Order By: Relevance
“…The wound healing assay and Transwell assays demonstrated that GAPLINC knockdown significantly inhibited the migratory and invasive abilities of bladder cancer cells. These observations may explain why GAPLINC was upregulated in MIBC tissues compared with NMIBC tissues, and were in agreement with the results of other studies (13,14) on gastric cancer and colorectal cancer.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The wound healing assay and Transwell assays demonstrated that GAPLINC knockdown significantly inhibited the migratory and invasive abilities of bladder cancer cells. These observations may explain why GAPLINC was upregulated in MIBC tissues compared with NMIBC tissues, and were in agreement with the results of other studies (13,14) on gastric cancer and colorectal cancer.…”
Section: Discussionsupporting
confidence: 92%
“…GAPLINC is associated with poor prognosis of gastric cancer and regulates gastric cancer cells invasiveness (13,22). GAPLINC also interacts with PTB-associated splicing factor (PSF) and non-POU domain-containing octamer-binding (NONO) protein, and ultimately promotes invasion in colorectal cancer (14). However, little is known about the association between GAPLINC and bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoform β interacts with PTENgp1 through RNA-RNA pairing, facilitates PTENgp1 export to the cytoplasm and modulates its stability and sponge activity (134). Function of gastric adenocarcinoma predictive large intergenic noncoding RNA (GAPLINC) is based on a sponge-related and RNA-protein related MOA (135,136). GAPLINC is associated with shorter survival in a subset of patients with gastric cancer, which overexpress this lncRNA (135).…”
Section: Metastasis-related Lncrnas: Category IImentioning
confidence: 99%
“…Recently, several studies have revealed that lncRNAs are dysregulated in numerous types of human cancers, including gastric, colorectal, gastric, ovarian, lung and breast cancer (2)(3)(4)(5)(6)(7). Certain lncRNAs have multiple functions in a wide range of biological processes, including proliferation, apoptosis, or cell migration (2,3,6).…”
Section: Introductionmentioning
confidence: 99%